Impact of Thresher Drum Rotation in Removing Palm Fruit from Boiled Fruit Bunches (TBR) - Tri Astina Pangaribuan; Winfronstein Naibaho (Journal of Engineering Science and Technology Management, 2026)
The effectiveness of palm fruit release at the Thresher station is greatly influenced by the stability of the drum rotation speed. However, operational conditions at PTPN IV Kebun Mayanng indicate instability of rotation due to variations in fruit size and fluctuations in the energy supply from the Boiler, so that the threshing process does not always occur optimally. This study aims to analyze the effect of the Thresher drum rotation speed on the ability to release palm fruit from the bunch and its impact on fruit damage under field conditions. The research method uses a mixed approach through direct observation at the Thresher station and quantitative measurements at three rotation variations, namely 20, 23, and 26 RPM. The measurement results are then analyzed qualitatively based on actual operational conditions. The results show that a speed of 23 RPM is the most stable rotation, resulting in effective fruit release with an acceptable level of fruit damage. A rotation of 20 RPM provides lower fruit damage, but causes less optimal fruit release and increases the number of fruit left on empty bunches. Meanwhile, a rotation of 26 RPM is able to increase the effectiveness of release, but causes very high fruit damage due to the influence of excessive centrifugal force. Overall, this study demonstrates a trade-off between release efficiency and fruit damage. Too high a rotation speed increases release efficiency but increases fruit damage, while too low a rotation speed decreases release efficiency and increases loss, albeit with less damage